MINIMASI DEFECT PADA PROSES PRODUKSI PAINTING MENGGUNAKAN METODE SIX SIGMA DI PT. UNI ALLOYINDO PRIMA - Supratman, Jasan; Saputro, Reyhan Apriliano (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2025)
PT Uni Alloyindo Prima is one of the industrial companies engaged in the manufacture of four-wheeled wheels with an average defect percentage of 1.5% where the company has a defect standard of 1%. The purpose of this study is to identify the factors that cause defects in the painting production process and determine how to minimize the occurrence of defects. In this study the method used is Six Sigma, the Six Sigma method has five main steps, namely define, measure, analyze, improve and control. The results showed that the dominant root causes of porosity defects in the painting production process are lack of checking on raw materials (materials), Pin-Hole defects are less careful when doing work (humans), lathe defects and grebes lack of maintenance on machines or work tools. After calculating the Sigma value after the improvement process is carried out, it reaches 4.63 from the one before the improvement is only 4.43.